Condition of epidermis and epidermal-dermal skin connection in patients with psoriasis and essential hypertension - G. I. Makurina (Zaporozhye State Medical University, 2016)
Background. Issues of lesion pathomorphogenesis in epithelial component of the skin in patients with psoriasis and hypertension on the background of the skin involutive changes requires clarification and further development. The aim of research is to determine the structural damage to epidermis in psoriasis patients depending on the presence or absence of hypertension. Materials and methods. In 60 patients skin biopsies were studied using light-optical microscopy. Quantitative morphological study was conducted using software package ImageJ 1,47v and common principles of morphometric analysis. Results. Morphological examination of the skin condition in elderly patients of the control group revealed typical involutive changes in the epidermis. In particular, the epidermis on the surface of smoothed papillae was unevenly thinned. The maximum total thickness of basal, spinous and granular layers was 41,7 ± 5,1 µm, the minimum - 26,3 ± 3,6 µm. In the loci of thinning (above the tips of papillae) cell ratio in layers of epidermis remained without pathological features. Conclusion. It was found that the morphological substrate of epidermal damage in patients with psoriasis and hypertension is a complex of local violations of the epithelial structure of the skin component: perifocal hyperplasia and degeneration of keratinocytes with acantholysis and destruction of the dermal-epidermal connection, including fragmentation of the basement membrane of the epidermis. This triggers the cascade of typical pathomorphological changes which intensity is significantly higher than the skin lesions in psoriasis patients without hypertension. In the active phase of psoriasis presence of hypertension aggravates the degree of local damage of the epidermis, strengthening the development of hyperkeratosis, parakeratosis, papillomatous hyperplasia, extracellular and cytoplasmic edema of epidermocytes, separation and detachment of the epidermis due to extravasations, Munro's microabscesses, leukocyte infiltration, erythrodiapedesis, and hemorrhage. Psoriasis; Essential Hypertension; Skin; Epidermis; Morphology